Frequency spectrum of focused broadband pulses of electromagnetic radiation generated by polarization currents with superluminally rotating distribution patterns. - Ardavan, H; Ardavan, A; Singleton, J (Optical Society of American (OSA), 2003)
We investigate the spectral features of the emission from a superluminal polarization current whose distribution pattern rotates (with an angular frequency omega) and oscillates (with a frequency omega > omega differing from an integral multiple of omega) at the same time. This type of polarization current is found in recent practical machines designed to investigate superluminal emission. Although all of the processes involved are linear, we find that the broadband emission contains frequencies that are higher than omega by a factor of the order of (omega/omega)2. This generation of frequencies not required for the creation of the source stems from mathematically rigorous consequences of the familiar classical expression for the retarded potential. The results suggest practical applications for superluminal polarization currents as broadband radio-frequency and infrared sources.